COLLABORATIVE GOVERNANCE IN BIRTH CERTIFICATE SERVICES (COOPERATION BETWEEN AIRLANGGA HOSPITAL AND DISPENDUKCAPIL SURABAYA CITY) - Ramadhan, Feri; Roekminiati, Sri; Devy Pramudiana, Ika; Sri Lestari, Damajanti (Proceeding of International Conference on Multidisciplinary Research, 2024)
Basically, the function of government administration is to provide excellent public services, both from the lowest to the highest levels in the world of government. Collaborative governance is one of the new strategic models of government that involves various stakeholders or stakeholders simultaneously in a forum with government officials to make joint decisions aimed at solving problems that cannot be faced alone by the government itself. This research was prepared to find out how the collaborative governance process of birth certificate services by Dispendukcapil Surabaya City, whether this program has been running well and to find out what are the supporters and obstacles as well as the advantages of the process of running a program that involves several parties. The analysis technique used in this research is descriptive technique. The research was conducted by collecting data through direct interviews to hospitals in the city of Surabaya. The method used is descriptive qualitative which conveys data in a narrative manner through other people's words, quotations, various texts, or other discourses. The results showed that the supporting factors for the course of this activity were the support of partners such as urban villages, sub-districts, hospital employees, the community, mass media, and other agency ranks who trusted each other. Then the inhibiting factors that lead to lack of human resources, people who do not understand, and also technical obstacles such as communication technology and information media that are not complete enough. There needs to be special attention related to sufficient infrastructure and human resources in the process of issuing birth certificates so that it runs quickly and efficiently.